Conditional risk of relapse in patients with germ cell testicular tumors: personalizing surveillance in clinical stage 1 disease. Issue 5 (September 2018) - Goldberg, Hanan; Madhur, Nayan; Hamilton, Robert J.
Abstract : Purpose of review: Germ cell testicular tumors (GCTTs) are the most common malignancy in young men, and the incidence is increasing worldwide. Most patients present with clinical stage I (CS1) disease, and active surveillance is being increasingly adopted as the preferred initial treatment modality. In this review, we describe the concept of conditional risk of relapse (CRR), an evolving risk estimate for CS1 GCTT patients on active surveillance who have not relapsed. Recent findings: At diagnosis, patients are often counseled about their initial risk of relapse based on known risk factors present at diagnosis. However, the risk estimate becomes less informative in patients who have survived a period of time without experiencing relapse. CRR, on the other contrary, provides specific information on a patient's evolving risk of relapse over time. This dynamic estimate can be used to tailor surveillance protocols based on future risk of relapse within risk subgroups. Summary: Implementation of CRR in patients on active surveillance can reduce the burden of follow-up, the number of physician visits and tests, and lower costs for the healthcare system. Finally, CRR estimates provide patients with a meaningful, evolving risk estimate, and may help reassure patients and reduce potential anxiety while continuing active surveillance.